Mixed-Methods Evaluation of the Washington State Practice Transformation Support Hub. Issue 5 (September 2021) - Kwan-Gett, Tao Sheng; Albertson, Elaine Michelle; Banks, Jordan; Revere, Debra; Rogers, Megan; Baseman, Janet; Andris, Lydia; Conrad, Douglas
Abstract : Purpose: Practice transformation initiatives have the potential to promote collaborations between public health, primary care, and behavioral health, but limited empirical evidence is available on how these programs affect participating clinical practices. Objective: To report the findings from a mixed-methods program evaluation of the Washington Practice Transformation Support Hub (Hub), a publicly funded, multicomponent practice transformation initiative in Washington State. Design: We used quantitative and qualitative methods to evaluate the impact of Hub activities on participating primary care and behavioral health practices. Pre- and posttest survey data were combined with administrative program data to understand the effect of program components. Qualitative interviews contextualized findings. Setting: Urban and rural primary care and behavioral health practices in Washington State. Participants: One hundred seventy-five practices that were recruited to receive Hub coaching and facilitation from 8 coaches; of these, 13 practices and all coaches participated in key informant interviews. Intervention: Practice coaching and facilitation supported by an online resource portal, from January 2017 through January 2019. Main Outcome Measures: Self-reported progress in specific activities in 3 practice-level domains: bidirectional integration of physical and behavioral health care (care integration); alignment with community-based services for whole-person care (clinical-community linkages); and value-based payment. Results: Participation in Hub activities was associated with improvements in care integration and clinical-community linkages but not with progress toward value-based payment. Qualitative results indicated that practice progress was influenced by communication with practices, the culture of the practice, resource constraints (particularly in rural areas), and perceptions about sustainability. Conclusions: This statewide practice transformation initiative was successful in strengthening primary care and behavioral health integration and clinical-community linkages among participating practices but not value-based payment. Future practice transformation efforts may benefit from addressing barriers posed by communication, limited application of value-based payment, culture change, competing priorities, and resource limitations, particularly for rural communities.